Quantum decoherence of neutrino mass states (Письма в ЭЧАЯ, 2024)
We study the interplay of the neutrino quantum decoherence and bipolar collective neutrino oscillations. Using the numerical simulation of the neutrino evolution in a supernova environment we show the suppression of the bipolar collective neutrino oscillations by the quantum decoherence of the neutrino mass states.